2021
DOI: 10.1111/infa.12404
|View full text |Cite
|
Sign up to set email alerts
|

Language familiarity influences own‐race face recognition in 9‐ and 12‐month‐old infants

Abstract: During their first year, infants attune to the faces and language(s) that are frequent in their environment. The present study investigates the impact of language familiarity on how French-learning 9-and 12-month-olds recognize own-race faces. In Experiment 1, infants were familiarized with the talking face of a Caucasian bilingual German-French speaker reciting a nursery rhyme in French (native condition) or in German (non-native condition). In the test phase, infants' face recognition was tested by presentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…These findings are particularly striking, because it is now wellestablished that other-race faces presented without language or other associated stimuli are not recognized by infants of these ages, due to perceptual narrowing (Kelly et al, 2007(Kelly et al, , 2009. In a previous study, we found that an own-race face recognition is tampered/ hindered when the face is associated with a non-native language (de Boisferon et al, 2021). The present results are in contradiction with the LFE, since associating a familiar native language with other-race faces did not improve their recognition.…”
Section: Main Findingmentioning
confidence: 61%
See 4 more Smart Citations
“…These findings are particularly striking, because it is now wellestablished that other-race faces presented without language or other associated stimuli are not recognized by infants of these ages, due to perceptual narrowing (Kelly et al, 2007(Kelly et al, , 2009. In a previous study, we found that an own-race face recognition is tampered/ hindered when the face is associated with a non-native language (de Boisferon et al, 2021). The present results are in contradiction with the LFE, since associating a familiar native language with other-race faces did not improve their recognition.…”
Section: Main Findingmentioning
confidence: 61%
“…Our main finding is that other-race faces can still be recognized by 9-and 12-month olds when associated with a non-native language. This finding challenges the conception of ORE during infancy, showing that multimodal presentation of the other-race face, as long as it does not violate infants' prior, can help overcoming the ORE. Alternatively, previous studies (de Boisferon et al, 2021;Minar & Lewkowicz, 2018) showed that any multimodal association considered as incongruent by the infants will impair face processing. It is thus possible that from 9 months of age, representations of social partners are multimodal, including language and faces.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations